Resistencia y compromiso de las mujeres antifascistas / Anti-Fascist Women’s Resistance and Commitment - Alcón Sornichero, Eva (Asparkía. Investigació feminista, 2013)
R RESUMEN La Agrupación de Mujeres Antifascistas constituyó un claro ejemplo de movilización de mujeres en la España de la Segunda República, con representación nutrida en diversas localidades de Castellón. Estas mujeres se organizarían en redes de resistencia para ayudar al Gobierno del Frente Popular a ganar la guerra, luchando desde la retaguardia contra el fascismo en diversos ámbitos. Y conformarán uno de los primeros movimientos de concienciación feminista, denunciando y combatiendo la sociedad patriarcal tantofuera como dentro de las propias organizaciones de la izquierda. Será precisamente bajo la coyuntura de la Guerra Civil cuando adquieran mayor protagonismo y libertad de acción, al tener que asumir roles y trabajos que hasta ese momento habían pertenecido en exclusividad a los hombres. Sin embargo, sus esperanzas de alcanzar una sociedad más igualitaria quedarán frustradas con la victoria del fascismo, que reduciría a las mujeres bajo un estado tiránico alimentado con la sumisión de éstas. Palabras clave: mujeres, antifascismo, emancipación, Guerra Civil, solidaridad, machismo, lucha, retaguardia. ABSTRACT The Agrupación de Mujeres Antifascistas (Anti-Fascist Women’s Group) was an illustrative example of the women’s mobilization during the Second Republic in Spain, a considerable number of members in various towns in the province of Castellón. These women organised themselves into resistance networks to help the Frente Popular Government win the war, by fighting against fascism in the rearguard and in various fields. They ended up forming one of the first feminist awareness movements, as they condemned and fought the patriarchal society both inside the leftwing organisations thernselves and outside them. It was under the very circumstances aeated by the Spanish Civil War that they took on a more prorninent role with greater freedom of action, as they had to take on positions and tasks which had until then exclusively belonged to men. However, their hopes of achieving a more egalitarian society were shattered by the victory of fascism, which would subsequently subjugate women under a tyrannical state nurtured by their own submission. Key words: women, anti-fascism, emancipation, Spanish Civil War, solidarity, male chauvinism, fight, rearguard.